2016
DOI: 10.23846/sr51180cida
|View full text |Cite
|
Sign up to set email alerts
|

Business support for small and medium enterprises in low- and middle-income countries

Abstract: The International Initiative for Impact Evaluation (3ie) is an international grant-making NGO promoting evidence-informed development policies and programmes. We are the global leader in funding, producing and synthesising high-quality evidence of what works, for whom, why and at what cost. We believe that better and policy-relevant evidence will make development more effective and improve people's lives. 3ie systematic reviews 3ie systematic reviews appraise and synthesise the available high-quality evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Nonetheless, some evidence is available on successful interventions to increase demand for labor in modern non-agricultural firms. 11 In a systematic review for 3ie, Piza et al, (2016) argue that impact evaluation evidence shows that business support services for small and medium enterprises (SMEs)training, management support, credit lines, innovation policies, and interventions that encourage firms to coordinate to realize agglomeration externalities-do increase employment, where that outcome has been measured. They also found that the number of impact evaluations is small and the interventions too heterogeneous to tease out which ones are more effective.…”
Section: Evaluation Results: Demand-side Interventions For Wage Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, some evidence is available on successful interventions to increase demand for labor in modern non-agricultural firms. 11 In a systematic review for 3ie, Piza et al, (2016) argue that impact evaluation evidence shows that business support services for small and medium enterprises (SMEs)training, management support, credit lines, innovation policies, and interventions that encourage firms to coordinate to realize agglomeration externalities-do increase employment, where that outcome has been measured. They also found that the number of impact evaluations is small and the interventions too heterogeneous to tease out which ones are more effective.…”
Section: Evaluation Results: Demand-side Interventions For Wage Employmentmentioning
confidence: 99%
“…Although the McKenzie and Woodruff (2013) review of business training interventions is a key systematic review, it did not cover employment outcomes at all.11 In this section, a large share of the evidence comes from middle income countries. The applications to lower income countries are highlighted.12 Similar to the supply-side interventions, a number of the demand-side programs included in thePiza et al, (2016) study used multiple interventions, making it difficult to determine which one actually made a difference.…”
mentioning
confidence: 99%
“…King, Samii, and Snilstveit 2010), or assess the applicability of findings in particular contexts (e.g. Piza et al 2016). • Similarly, the purpose of sequential exploratory design in the context of a systematic review of effects is for the qualitative findings to inform the quantitative data collection instruments and/or approach to synthesis.…”
Section: Approach To Assess Incorporation Of Qualitative Evidence In Srs Of Effectsmentioning
confidence: 99%
“…Due to the prevalence of studies of matching grants, they are one of the few PSD instruments that have been systematically analysed, with evidence showing a positive effect on firm performance and employment creation (Piza et al, 2016). Piza et al's (2016) meta-analysis found matching grants to have a positive effect size of 0.12 standard deviations on employment creation. Figure 2 shows the effect size of each on employment of each of the study's included in Piza et al's (2016) meta-analysis sample.…”
Section: Matching Grantsmentioning
confidence: 99%
“…empirically, but there is limited evidence of the impacts of non-traditional and innovative financing instruments (Mallen & Bungey, 2019;Piza et al, 2016). Of those financial instruments that have been systematically reviewed, matching grants, technical assistance and tax simplification have been found to positively affect firms' performance and job creation, and technical assistance has been found to improve labour productivity (Piza et al, 2016).…”
mentioning
confidence: 99%